Analisis Kesiapan Auditor dalam Mengadopsi Artificial Intelligence - Afriani, Alfina; Wawo, Andi; Sari, Nur Rahma (ISAFIR: Islamic Accounting and Finance Review, 2024)
This research aims to understand auditors' perceptions and readiness towards the adoption of Artificial Intelligence (AI) in the audit process based on the theory of planned behavior. This research uses a qualitative method with a phenomenological approach, focusing on auditors at KAP Ardaniah Abbas located at Jl. Barombong No. 240, Bonto Pajja, Kec. Barombong, Gowa. The research data consists of primary data, obtained through interviews, and secondary data from books and other references. Data analysis was conducted through three stages: data reduction, presentation of research results, and conclusion drawing. The results of this study reveal that auditors at KAP Ardaniah Abbas have a positive perspective and attitude towards the adoption of AI in the audit process. Support from regulators and colleagues is considered a factor that increases motivation to adopt AI. In addition, the availability of training, adequate IT knowledge, and supportive software and hardware infrastructure also play an important role in encouraging the adoption of AI by auditors.